A206 INVESTIGATING IBD TRANSITION READINESS AND FAMILY DYNAMICS: THE ADOLESCENT AND PRIMARY CAREGIVER PERSPECTIVE. (15th March 2019) - MacDonald, J; Heisler, C; Otley, A; Currie, B; Phalen-Kelly, K; Jones, J
Abstract: Background: Inflammatory Bowel Disease (IBD) is a chronic, immune-mediated disease that can lead to significant burden for both patients and families, with rates of childhood IBD rapidly increasing. Similar to other childhood chronic diseases, the transition between pediatric and adult care services can be challenging for patients and families and has been associated with poorer health outcomes immediately following transfer. This aspect of care is still a relatively new integration into IBD care and there are limited evidence-based approaches to appropriately support patients and their families during this transition. Aims: The aim of this study was to describe the relationship between the quality of parent-child relationships and patient readiness to transition to adult care. Methods: This was an exploratory study that employed a cross-sectional design whereby participants were recruited in transition clinics held at a tertiary care pediatric hospital in Nova Scotia. Adolescent participants completed three questionnaires: Transition Readiness Assessment Questionnaire (TRAQ), Successful Transition to Adulthood with Therapeutics (STARX), and PROMIS Pediatric Family Relationships Questionnaire. Parent participants completed two questionnaires: STARX Parent proxy and the PROMIS Parent Family Relationships Questionnaire. Spearman correlations were used to determine potential associations between pediatric and parent transition readiness, as well as assess the patient-parent relationship. Results: A total of 16 patient-parent dyads were recruited, with recruitment ongoing until December 2018. Adolescents had a mean age of 17.56 years (SD=0.51 years). The mean overall TRAQ-Adol score was 71.27 (SD=18.70, range 35–102). The mean overall STARX-Adol score was 53.47 (SD=7.75, range 43–70 points). The mean overall PROMIS-Adol score was 198.69 (SD=37.07, range 129–235 points). Parent STARX scores were similar, with a mean overall score of 51.75 (SD=8.14, range 27–66 points). The mean PROMIS-parent score was 208.92 (SD=26.24, range 152–235 points). PROMIS-parent and STARX-parent scores were strongly correlated (Spearman's rho=0.80), however significant associations were lost in subsequent analyses with PROMIS-Adol, STARX-Adol, TRAQ, and STARX scores. Conclusions: The study demonstrated the influence of family relationships and different stakeholder perspectives on transition readiness. The strength of the association between parent scores of relationship quality and transition readiness further supports the notion that transition success can be attributed to the relationship between the adolescent and the parent. Within the clinical context, it may be valuable to incorporate transition readiness assessments and consider the adolescent-parent relationship into clinical care treatment plans. Funding Agencies: CAG, None